Character Building based on Multiple Intelligences Classroom for Elementary School in The Digital Era - Suci Ramadhanti Febriani; Yusnawati Yusnawati; Anasrudin Anasrudin (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2021)
Human resource development greatly determines the quality of education in the digital era. The integration of science, technology and character domains is one of the complex challenges in the era of globalization. This basis, the internalization of character values ​​from an early age is one of the important elements in facing challenges in the 21st century. This study aimed to explore character development through learning strategies based on the multiple intelligences classroom management. This study used a qualitative research approach with a case study method design at SD Plus Al-Kautsar Malang. The data obtained include observation, interviews and documentation related to the topic and data analysis used is data triangulation with three steps: data collection, reduction and conclusion. The results showed that the internalization of character values ​​can be generated through management classroom based on multiple intelligence; exemplary, courage, discipline, independence, responsibility and respect for others; while the strategy used is through the integration of science, technology and IMTAQ in the learning process in the digital era. The findings showed that the integration of the learning process with classroom management based on multiple intelligences can internalize the character values ​​of students.